Efficacy of Fat Supplements with Different Unsaturated/Saturated FA Ratios Undergoing First Postpartum Ovulation in Lactating Anovulatory Goats - Caroline P. Silva; César C. L. Fernandes; Juliana P. M. Alves; Camila M. Cavalcanti; Felipe B. B. Oliveira; Alfredo J. H. Conde; Diana Celia S. N. Pinheiro; Darcio I. A. Teixeira; Anibal C. Rego; Davide Rondina (Veterinary Sciences)
We investigated whether microalgae or linseed supply during the early postpartum period affects ovarian restimulation and supports the first postpartum ovulation in lactating anovulatory goats. Thirty-eight An-glo-Nubian-crossbred adult goats were allocated into three groups, one with a control diet (n = 12), fed a total mixed ration (TMR) comprising chopped elephant grass and concentrate; an algal diet (n = 13), fed TMR + green microalgae (1% dry matter); and a linseed diet (n = 13), TMR + linseed (12% dry matter). Supplements were furnished from the second to fifth week (time of weaning). Goats were estrus synchronized on day 40 by insertion of an intravaginal CIDR device for 5 days, after which 0.075 mg PGF2α was applied to induce ovulation, and estrus was monitored for 72 h. From the 5th–15th day of ovulation induction, the corpus luteum (CL) area and progesterone rate were monitored. The algal and linseed groups showed lower feed intake (p < 0.001) and higher (p < 0.001) triglyceride levels/follicle numbers, respectively. After estrus induction, no differences were observed in estrus response; however, the linseed group showed more and larger growing follicles (p = 0.016 and p < 0.01), a higher ovulation rate (p < 0.05), a larger CL area (p < 0.05), and higher progesterone levels (p < 0.001). Linseed after delivery stimulates follicular growth before and after ovulation induction, favoring better CL quality during the first ovulation.